Efficient Information Retrieval: Tools for Knowledge Management - Schmid, Beat; Stanoevska-Slabeva, Katarina; Handschuh, Siegfried; Hombrecher, Alexis (My University, 1998)
Knowledge has become an important resource in many organisations. Thesuccess of an organisation depends on its ability to transform personal knowledge of employees into organisational knowledge. This knowledge can then be madewidely available to the entire organisation and be reused when needed.One necessary prerequisite for reusing knowledge, coded and stored indocuments, are appropriate classification and retrieval procedures. Classificationaccompanies the process of knowledge externalisation and retrieval supports the process of knowledge internalisation by enabling the capturing of appropriatecoded knowledge. In this paper we will evaluate currently available retrieval mechanism with respect to their effectiveness in knowledge management. We will then present a comprehensive classification and retrieval technology based on the Q-Technology, which provides support for the automated and intelligent classification and retrieval of knowledge.